Bukan Mitos tetapi Tidak Bertransmisi: Karakter Ideal Mahasiswa, Formasi Kelompok, dan Kooperativitas - Muwaffaq, Thafhan; Sabbah, Sherien; Pratiwi, Andhika (Universitas Al Azhar Indonesia, 2024)
This research reports findings about (i) social learning of norms and institutional rules about students ideal character, and (ii) group formation and normative behaviour among cooperating individuals within group. Researchers interviewed a number of sources and studied institutional documents, spread questionnaire to population of lecturers and conducted purposive sampling to students of Faculty of Humanities, University of Al-azhar Indonesia, and reviewed cases of students groupwork in a few courses held by English Language and Culture Study Programme. This research finds lecturers and students share the same idea about students’ ideal character; the idea tends to refer attitude and soft skills. However, the knowledge is not attained via social learning that transmits the idea as cultural information. This research finds group formation consequently establishes expectation of cooperative behaviour among the group members. Violating the expectation leads to social and institutional punishments. This research exemplifies an initial attempt to scrutinize cultural transmission and evolution in university.